2011
DOI: 10.1007/s10802-011-9543-1
|View full text |Cite
|
Sign up to set email alerts
|

Do Historical Changes in Parent–Child Relationships Explain Increases in Youth Conduct Problems?

Abstract: The coincidence of historical trends in youth antisocial behavior and change in family demographics has led to speculation of a causal link, possibly mediated by declining quality of parenting and parent-child relationships. No study to date has directly assessed whether and how parenting and parent-child relationships have changed. Two national samples of English adolescents aged 16-17 years in 1986 (N = 4,524 adolescents, 7,120 parents) and 2006 (N = 716 adolescents, 734 parents) were compared using identica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 60 publications
4
54
0
6
Order By: Relevance
“…Whereas there is evidence for the occurrence of numerous societal changes during the last decade [11,12,24,28], it can be questioned whether these changes were large enough to affect the proximal environment of adolescents known to more directly affect adolescents' emotional and behavioral problems (e.g., [22]). Gender differences in emotional and behavioral problems were also found to be relatively stable over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas there is evidence for the occurrence of numerous societal changes during the last decade [11,12,24,28], it can be questioned whether these changes were large enough to affect the proximal environment of adolescents known to more directly affect adolescents' emotional and behavioral problems (e.g., [22]). Gender differences in emotional and behavioral problems were also found to be relatively stable over time.…”
Section: Discussionmentioning
confidence: 99%
“…Recent decades have shown ample societal changes in Western countries with a potential positive or negative impact on the lives of adolescents (e.g., [11,12,24,28]). By means of time-trend studies on adolescent emotional and behavioral problems, possible effects of changing societies on the lives of adolescents can be detected.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the family structure and the child's age and gender are frequently discussed (15). Since the 1990s we have been able to observe a rising rate of divorces leading to more single-parent and stepparent households (16,17). Many research studies have shown that these changes in the composition of the family are critical to children's well-being and development (17,18).…”
Section: Intact Vs Step Familymentioning
confidence: 99%
“…Especially girls tend to experience more difficulties in talking with their fathers, both biological and stepfathers (24,30). This may be associated with the overall higher frequency and quality of time spent by boys with their family, especially with their fathers (16,31). Girls, in contrast, experience greater limitations on their freedom and higher levels of parental monitoring (16,32).…”
Section: Gender and Age Differencesmentioning
confidence: 99%
“…The past few decades have witnessed signiicant adaptations in parenting approaches globally, for example, see Refs. [5][6][7]. With changing times, it is not only the practices of parenting that are evolving but also the atachment paterns and perceptions encompassed, especially within a parent-adolescent relationship.…”
Section: Introductionmentioning
confidence: 99%